HONEY’S HEALTH BENEFITS ACCORDING TO THE QUR’AN: HONEY’S HEALTH BENEFITS ACCORDING TO THE QUR’AN - Hayati, Nur Ilmi (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2022)
Improving the immune system and reducing the risk of respiratory infection is vital during the deployment of the covid virus 19. Hence, we need to consume natural products like honey. The qur ’an of honey contains many medicinal properties for various diseases.